Bibliometric Analysis: Research Trend of Interactive Learning Media in Mathematics Learning in Indonesia - Ilham Muhammad; Ahmad Mukhibin; Abdurrahman do muhamad Naser; Dadan Dasari (IKIP Mataram, 2023)
Interactive learning media is a combination of videos, animations, images, and audio on learning media that allows users to interact and understand the material because the learning process becomes interesting, interactive, and effective. The trend of publications that have the highest number of citations, the classification of university or organization rankings, journals and publications, and the use of keywords along with using a database from Google Scholar. The method used is bibliometric analysis. A total of 442 articles were collected from the Publish or Perish (PoP) application using the Google Scholar database which was then combined into 1 file with RIS format and entered into the VOSviewer application to obtain network visualization and visualization overlays. The results show that the trend of publications related to interactive learning media in mathematics education in Indonesia in the last five years (2016 - 2022) has increased every year, the most citations are in the organization